Flexible, Scalable, and Highly Conductive Garnet‐Polymer Solid Electrolyte Templated by Bacterial Cellulose. Issue 18 (23rd March 2018) - Xie, Hua; Yang, Chunpeng; Fu, Kun (Kelvin); Yao, Yonggang; Jiang, Feng; Hitz, Emily; Liu, Boyang; Wang, Sha; Hu, Liangbing
Abstract: Solid‐state electrolytes are a promising candidate for the next‐generation lithium‐ion battery, as they have the advantages of eliminating the leakage hazard of liquid solvent and elevating stability. However, inherent limitations such as the low ionic conductivity of solid polymer electrolytes and the high brittleness of inorganic ceramic electrolytes severally impede their practical application. Here, an inexpensive, facile, and scalable strategy to fabricate a hybrid Li7 La3 Zr2 O12 (LLZO) and poly(ethylene oxide)‐based electrolyte by exploiting bacterial cellulose as a template is reported. The well‐organized LLZO network significantly enhances the ionic conductivity by extending long transport pathways for Li ions, exhibiting an elevated conductivity of 1.12 × 10 −4 S cm −1 . In addition, the hybrid electrolyte presents a structural flexibility, with minor impedance increase after bending. The facile and applicable approach establishes new principles for the strategy of designing scalable and flexible hybrid polymer electrolytes that can be utilized for high‐energy‐density batteries. Abstract : A hybrid Li7 La3 Zr2 O12 (LLZO) and polymer electrolyte is developed by exploiting bacterial cellulose as a template. The well‐organized LLZO network not only significantly enhances the ionic conductivity by extending long transport pathways for Li ions, but also exhibits structural flexibility. This approach establishes new principles for designing scalable and flexible hybrid electrolytes for lithium metal batteries.